2022
DOI: 10.1021/acsnano.1c10981
|View full text |Cite
|
Sign up to set email alerts
|

Gallium Nanodroplets are Anti-Inflammatory without Interfering with Iron Homeostasis

Abstract: Gallium (Ga) compounds, as the source of Ga ions (Ga3+), have been historically used as anti-inflammatories. Currently, the widely accepted mechanisms of the anti-inflammatory effects for Ga3+ are rationalized on the basis of their similarities to ferric ions (Fe3+), which permits Ga3+ to bind with Fe-binding proteins and subsequently disturbs the Fe homeostasis in the immune cells. Here in contrast to the classic views, our study presents the mechanisms of Ga as anti-inflammatory by delivering Ga nanodroplets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 58 publications
0
49
0
Order By: Relevance
“…In particular, researchers found that LM antimicrobial agents are not friendly to immunocompromised patients because prolonged use of Ga can lead to reduced immunity [ 134 ]. However, it is worth mentioning that one study has investigated that delivering LM nanodroplets into a macrophage is a potential way to modulate discrete signaling pathways, without interfering with Fe homeostasis from the usage of Ga 3+ [ 135 ]. This study sheds light on the mechanism of LM nanodroplets–macrophage interactions, potentially enabling more pathways for Ga to be used for future biomedical and pharmaceutical applications.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In particular, researchers found that LM antimicrobial agents are not friendly to immunocompromised patients because prolonged use of Ga can lead to reduced immunity [ 134 ]. However, it is worth mentioning that one study has investigated that delivering LM nanodroplets into a macrophage is a potential way to modulate discrete signaling pathways, without interfering with Fe homeostasis from the usage of Ga 3+ [ 135 ]. This study sheds light on the mechanism of LM nanodroplets–macrophage interactions, potentially enabling more pathways for Ga to be used for future biomedical and pharmaceutical applications.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Another recently proposed article of the exact opposite mechanism of anti-inflammatory action of classical Ga ions (Ga3+) via delivering Ga nanodroplets (GNDs) to lipopolysaccharide-induced macrophages. GNDs exerted a selective inhibition of NO generation without interfering with the accumulation of pro-inflammatory agents by disrupting the synthesis of inducible NO synthase in activated macrophages through up-regulation of eIF2α phosphorylation levels, without disturbing Fe homeostasis ( Zhang et al., 2022 ). A lipophilic Ga complex, Ga2L3(bpy)2, has both Ga (disruption of iron metabolism) and ligand effects (production of ROS) in the fight against drug-resistant bacteria ( Wang et al., 2021 ).…”
Section: Preventing Biofilm Formationmentioning
confidence: 99%
“…39 However, the present results essentially provide fundamental insights for the future design of nanocoating using Ga NPs with higher antibacterial activity. Lastly, considering that Ga ions also have an anti-inflammatory effect, 49 such nanocomposites with antioxidant and antibacterial properties have the potential to be applied to a wider range of biomedical applications including medical and implantable devices.…”
Section: Nanoscale Papermentioning
confidence: 99%